Decision Support System For Determining The Best Employee Using The Visekriterijumsko Kompromisno Rangiranje Method (Case Study At Distribution Center Guardian) - Auliyah, Risma; Maulana, Donny; Afriantoro, Irfan (Journal of Applied Intelligent System, 2023)
The quality of human resources is one of the supporting factors to increase the performance productivity of a corporate agency. Highly competent human resources can support the level of performance, with performance appraisal, the achievements of each employee will be obtained. To obtain fast and accurate information on employee performance that meets the expected criteria. To find out this, with a multi-criteria decision-making method by solving complex and unstructured situations into parts and compiling them using the Visekriterijumsko Kompromisno Rangiranje (VIKOR) method on Decision Support Systems (SPK), the determination of the best employee can be calculated based on the calculation of the weight their respective criteria, so that they can quickly select the best employees in the company. From the final results of the VIKOR method, ranking 1 is Sukron, with a value of 0.